Analysis of Effectiveness of Cut Size Line Machines Based on Total Productive Maintenance (TPM) and Analytical Hierarchy Process (AHP) - A Case Study - Muhammad Ardi; Agus Sutanto; Anita Susilawati (International Society of Ocean, Mechanical and Aerospace -scientists and engineers- (ISOMAse), 2023)
This research aims to analyze the implementation of Total Productive Maintenance (TPM) using Overall Equipment Effectiveness (OEE) and Analytical Hierarchy Process (AHP) approaches to increase the OEE value on cut-size line machines in the finishing department in PT. X. The research methodology was carried out by calculating OEE and significant loss values, analyzing Pareto and Fishbone diagrams, and using the AHP as a decision-making method. Then, the recommendations for implementing focused and autonomous maintenance in the case study company. The research results revealed that the significant influencing factor for the OEE value was engine speed, which causes performance efficiency to decrease so that the OEE value also decreases. The OEE value in 2021 is 74%. The improvement plan by applying the TPM and AHP methods will be expected to increase the performance efficiency of the machine via OEE value from 74% in 2021 to 79% for the coming year 2023/2024.